Editorial for the Proceedings of the 2015 E-MRS Spring Meeting Symposium C - Advanced Inorganic Materials and Structures for Photovoltaics. (December 2015) - Gordon, I.; Conibeer, G.; Krc, J.; Slaoui, A.; Niki, S.
Abstract: This paper contains the editorial of the proceedings of the 2015 E-MRS spring meeting symposium C on "Advanced Inorganic Materials and Structures for Photovoltaics".